2000
DOI: 10.1086/314031
|View full text |Cite
|
Sign up to set email alerts
|

Yellow Fever Vaccination of Human Immunodeficiency Virus-Infected Patients: Report of 2 Cases

Abstract: Yellow fever vaccine (17D, a live attenuated virus vaccine) was effective and safe in 2 human immunodeficiency virus-infected patients without severe immunosuppression, one of whom traveled to Kenya and the other of whom traveled to Senegal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(31 citation statements)
references
References 1 publication
1
29
0
Order By: Relevance
“…49 In both patients, a decrease in CD4 cell count of approximately 200 occurred in the first month after vaccination without any disease manifestation and with a steady recovery. The retrospective study conducted by Tattevin and others also showed favorable efficacy results for a 17DYF vaccine in HIV-infected patients with CD4 cell counts 200 cells/mm 3 .…”
Section: Americanmentioning
confidence: 81%
See 1 more Smart Citation
“…49 In both patients, a decrease in CD4 cell count of approximately 200 occurred in the first month after vaccination without any disease manifestation and with a steady recovery. The retrospective study conducted by Tattevin and others also showed favorable efficacy results for a 17DYF vaccine in HIV-infected patients with CD4 cell counts 200 cells/mm 3 .…”
Section: Americanmentioning
confidence: 81%
“…Four retrospective observational studies reported a good immunologic response in HIV patients with CD4 cell counts 200 cells/mm 3 and variable viral load. [49][50][51][52] The seroconversion rates were high (92-100%) although the number of persons included in the analysis was small in three of the studies (2, 12, and 14 respectively).…”
Section: Americanmentioning
confidence: 97%
“…Pacanowski and others 37 reported on 103 patients at the Hô pital Saint Antoine, Paris, France. Receveur and others 38 reported two case reports from a travel clinic in Bordeaux, France. Tattevin and others 39 reported on 12 patients at Pontchaillou Hospital, Rennes, France.…”
Section: Resultsmentioning
confidence: 99%
“…These include oral polio vaccine, vaccinia, bacillus Calmette-Guerin, and live oral typhoid (11). Although yellow fever vaccination has been used in case reports with human immunodeficiency virus infection (86), no data are available in solid-organ recipients. In our opinion the vaccine should be considered contraindicated.…”
Section: Live Vaccinesmentioning
confidence: 99%